2020
DOI: 10.1002/jcsm.12531
|View full text |Cite
|
Sign up to set email alerts
|

AdipoRon, a new therapeutic prospect for Duchenne muscular dystrophy

Abstract: Background Adiponectin (ApN) is a hormone known to exhibit insulin-sensitizing, fat-burning, and anti-inflammatory properties in several tissues, including the skeletal muscle. Duchenne muscular dystrophy (DMD) is a devastating disease characterized by dystrophin deficiency with subsequent chronic inflammation, myofiber necrosis, and impaired regeneration. Previously, we showed that transgenic up-regulation of ApN could significantly attenuate the dystrophic phenotype in mdx mice (model of DMD). Recently, an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(58 citation statements)
references
References 63 publications
3
55
0
Order By: Relevance
“…Some of these beneficial effects of ApN/AdipoRon have been translated to humans. We found that ApN/AdipoRon supplementation retained its anti-inflammatory properties in DMD human myotubes [56,57,103] and induced a shift in the secretion of downstream myokines toward a less inflammatory profile. Indeed, secretome analysis from myotubes revealed that ApN down-regulated the secretion of two pro-inflammatory factors (TNFα and IL-17A), one soluble receptor (sTNFRII), and one chemokine (CCL28) [57].…”
Section: Duchenne Muscular Dystrophymentioning
confidence: 75%
See 4 more Smart Citations
“…Some of these beneficial effects of ApN/AdipoRon have been translated to humans. We found that ApN/AdipoRon supplementation retained its anti-inflammatory properties in DMD human myotubes [56,57,103] and induced a shift in the secretion of downstream myokines toward a less inflammatory profile. Indeed, secretome analysis from myotubes revealed that ApN down-regulated the secretion of two pro-inflammatory factors (TNFα and IL-17A), one soluble receptor (sTNFRII), and one chemokine (CCL28) [57].…”
Section: Duchenne Muscular Dystrophymentioning
confidence: 75%
“…dye solution into muscles mirrored the strengthening of sarcolemmal integrity [56]. All these beneficial effects of ApN have recently been reproduced by AdipoRon, an agonist of ApN receptor given orally for 2 months to young mdx mice [103] (see Section 6.3).…”
Section: Duchenne Muscular Dystrophymentioning
confidence: 96%
See 3 more Smart Citations